1973
DOI: 10.1113/jphysiol.1973.sp010274
|View full text |Cite
|
Sign up to set email alerts
|

Long‐lasting potentiation of synaptic transmission in the dentate area of the unanaesthetized rabbit following stimulation of the perforant path

Abstract: 7. During the long-lasting potentiation there was an increase in the excitability of the post-synaptic cells and, on some but not all occasions, an increase in the extracellular current flow produced directly by synaptic action. 358

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
546
3
9

Year Published

1996
1996
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,303 publications
(587 citation statements)
references
References 2 publications
12
546
3
9
Order By: Relevance
“…Although we conducted our lowfrequency and high-frequency stimulation experiments in different groups of rats, the possibility that signals decayed only in the rats receiving high-frequency stimulation, and not in those receiving low-frequency stimulation, under similar experimental conditions, is very unlikely. Third, similar to what others have found in the DG (Bliss and Gardner-Medwin, 1973), we also observed that rats showed potentiation that lasted almost three times longer when the number of high-frequency stimulation trains was doubled (data not shown), indicating that LTP decay is specific to tetanization parameters. Fourth, as has been previously suggested (Staubli and Lynch, 1987), decay in recording conditions over time in even a small number of animals would be expected to mask response stability in the majority of rats.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Although we conducted our lowfrequency and high-frequency stimulation experiments in different groups of rats, the possibility that signals decayed only in the rats receiving high-frequency stimulation, and not in those receiving low-frequency stimulation, under similar experimental conditions, is very unlikely. Third, similar to what others have found in the DG (Bliss and Gardner-Medwin, 1973), we also observed that rats showed potentiation that lasted almost three times longer when the number of high-frequency stimulation trains was doubled (data not shown), indicating that LTP decay is specific to tetanization parameters. Fourth, as has been previously suggested (Staubli and Lynch, 1987), decay in recording conditions over time in even a small number of animals would be expected to mask response stability in the majority of rats.…”
Section: Discussionsupporting
confidence: 90%
“…Multiple lines of evidence indicate that LTP is one mechanism underlying learning and memory processes in the central nervous system (Morris et al, 1986;Moser et al, 1998). Like memory, LTP can be induced within seconds, it may last for hours, days, or weeks (Bliss and Gardner-Medwin, 1973), and it shows a consolidation period that lasts for minutes after induction (Barrionuevo et al, 1980). Indeed, the persistence of LTP has been regarded as an important characteristic of its usefulness as a memory mechanism and the long duration over which LTP can be observed in intact animals makes it a good model of memory (Abraham et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…LTP was first described in the hippocampus of anesthetized and behaving animals [19,20], and there has been much evidence that acetylcholine modulates hippocampal LTP. Application of the cholinergic agonists enhanced hippocampal LTP in vitro [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Induction of hippocampal long-term potentiation (LTP), a cellular model of neural plasticity (Bliss and Lomo 1973), has been shown to require the activation of NMDA receptors. On the other hand, antagonists of the NMDA receptors; for example, AP5, MK-801 (dizocilpine), and phencyclidine (PCP) have been shown to block hippocampal LTP in vitro and to impair hippocampal-dependent behavior; for example, place and spatial learning (Bischoff and Tiedtke 1992;Coan et al 1987;Eichenbaum et al 1990; Morris et al 1986).…”
mentioning
confidence: 99%